Pengaruh Aditif Dalam Larutan Watts Buffer Sitrat Terhadap Karakteristik Deposit Nikel Pada Proses Pelapisan Baja Karbon Rendah [The Influence of Additive on Watts Buffer Sitrate Solution to The Nickel Deposition Characteristic on Low Carbon Steel Plating Process] - Widyanto, Bambang; Idamayanti, Dewi (Jurnal Metalurgi, 2016)
Research on the substitution of boric acid with citric acid in Watts electrolyte for nickel electroplating on low carbon steel has been conducted. Nickel was deposited on low carbon steel by electroplating method at 50 °C, pH 4, and the current density 0,17A / cm2 for 5 minutes. The additives that used to produce a bright nickel deposit are sodium lauryl sulfate as a surfactant, saccharin and 2-butyne-1,4- diol as a brightener. The results showed Watts citrate buffer solution can increase the hardness of nickel deposits up to 431 ± 9 VHN, deposits tend to be more brittle and generate porosity. Lauryl sulfate 0.08 g / L can effectively eliminate porosity, slightly increase the hardness of the deposit be 482 ± 4 VHN and tend to be more resilient. Synergies saccharin and 2-butyne-1,4-diol (1.5 to 0.15 g/L) as the brightener produces bright surface and harden up to 587 ± 6 VHN. Adhesion to deposit nickel on low carbon steel is relative strong which has been proved by performing bend test. The use of brightener can play a role as well as grain refinement in the coating process. It is shown by the results of morphological observation surface of nickel deposit that deposit grains with brightener is finer than without brightener. The thickness of deposit can not fully be homogeneous which the middle area is thicker 6.8 to 11 μm than the edge 12-33 μm.